PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION BERBASIS INTERNET TERHADAP HASIL BELAJAR DAN KEMAMPUAN DIGITAL LITERASI SISWA PADA PEMBELAJARAN IPS - Sai, M. (Jurnal Penelitian Pendidikan, 2017)
The purpose of this study was to analyze: (1) the difference between students who take internet-based learning group investigation with students who take the group investigation learning library based on improving student learning outcomes; (2) the difference between students who take internet-based learning group investigation with students following study group investigation based library of digital literacy to increase the ability of students.This research is a quasi experiment with non equivalent control group design. The variables in this study included the independent variable in the form of model of learning and investigation group namely internet-based moderator variable and the dependent variable of the ability of digital literacy of students. The population in this study were junior high school students KHM. Nur Surabaya, with a sample of students in grade 8 -A and 8 - C. The instrument used is a matter of pretest and posttest material capabilities IPS, observations, and questionnaires digital literacy abilities of students. Data were analyzed using ANOVA test and test two paths independent sample t - test (with significance level of 5 %). The results showed that: (1) Increasing the learning outcomes of students who received internet-based learning group investigation is higher than the students obtain a library-based learning group investigation. (2) Increasing the capability of digital literacy of students who received internet-based learning group investigation is higher than the students obtain a library-based learning group investigation